The Influence of Foreign Portfolio Investment and Public Ownership on Stock Price Volatility of Indonesian Energy Sector Companies (2021–2024) - Vania Nur Faith; Eni Wuryani (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study examines the effect of Foreign Portfolio Investment (FPI) and public ownership structure on the stock price volatility of energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative approach, this research analyzes secondary data from 40 companies, resulting in 160 observations. Data were collected from annual reports, Indonesia Stock Exchange publications, and stock price records and analyzed using panel data regression. The results show that Foreign Portfolio Investment and Foreign Institutional Ownership has a negative effect on stock price volatility. In contrast, Local Institutional Ownership and Foreign Individual Ownership has a positive effect on stock price volatility, while Local Individual Ownership has no effect on stock price volatility. These findings indicate that different investor groups contribute differently to stock price movements. This study concludes that investor heterogeneity plays an important role in explaining stock price volatility in Indonesia’s energy sector.